Relationship Between Online Food Ordering Time and Physical Activity With The Nutritional Status of Students at Medan Area University - harahap, Laila Apriani hasanah; Kusuma Wardhani, Eva Flourentina (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2023)
The emergence of online food ordering applications. Currently, it is widely used by various groups of people including students. With the online food ordering application, it provides convenience in mobilization and in ordering food. The negative impact of using online applications is that there will be reduced physical activity used to buy food. Low physical activity will have an impact on increasing the risk of non-communicable disease incidence. Excessive eating patterns, carried out at inappropriate times (night) and lack of physical activity can cause poor metabolism so that it will cause more nutrition. The type of research used is descriptive research, with a cross-sectional research design, using the survey method. The population is students of the faculty of economics at Medan Area University. The sampling technique used is nonprobability sampling with incidental sampling technique, which is a sampling technique based on chance, that is, anyone who by chance or incidentally meets the researcher can be used as a sample, if it is seen that the person who happened to be met is suitable as a data source. The number of samples in this study were 100 respondents. Based on the results of the analysis using the Chi-Square test, it is known that research on the relationship between online food ordering time and physical activity with nutritional status explains that the value of p = 0.004 (physical activity) and p = 0.006 (online ordering time).